Consumption of hogplum (Spondias mangifera) leaflet by immature and adult stages of hogplum beetle (Podontia 14-punctata L) under laboratory condition - Khan, MMh (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not available Jahangirnagar University J. Biol. Sci. 5(1): 101-104, 2016 (June)